2010
DOI: 10.1007/s12008-010-0094-4
|View full text |Cite
|
Sign up to set email alerts
|

Virtual representation of terrain through the web with VRML-Web3D and graphic libraries

Abstract: This paper is focused on the analysis of virtual representation of terrain through the web, and shows the steps to follow in order to put into practice a virtual interactive terrain visualization system. The recent developments of threedimensional visualization systems can be naturally applied to terrain visualization targeted to the web, driving to a higher interaction level. Traditionally it has been implemented with 2D systems due to the huge data volume involved, but nowadays several possible technologies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Martinez et al (43) used VRML as an exponent of Web3D technology to analyze virtual terrain representation on the web. They found that VRML needs support from a graphic engine to overcome problems with handling the program (code).…”
Section: Online Visualization Of 3d Terrainmentioning
confidence: 99%
“…Martinez et al (43) used VRML as an exponent of Web3D technology to analyze virtual terrain representation on the web. They found that VRML needs support from a graphic engine to overcome problems with handling the program (code).…”
Section: Online Visualization Of 3d Terrainmentioning
confidence: 99%
“…Digital museums can simulate a real museum in 3D through virtual reality technology. Web3d is a kind of virtual reality technology based on a 3D internet platform [4] that displays objects tangible in the real world on the internet and supports interaction between users and virtual objects [5]. Web3d originating from Virtual Reality Modeling Language ( VRML) in the internet can be traced back to the 1990s [6].…”
Section: Introductionmentioning
confidence: 99%
“…Atmosphere is used directly in the Viewpoint Technology. VRML technology is not flexible in interaction design [4][5][6][7]. In a word, the Cult3D technology is currently the best solution on three-dimensional display of merchandise online.…”
Section: Introductionmentioning
confidence: 99%